A genetic approach to study mating system on Jabon Merah (Anthocephalus macrophyllus Roxb.) from three different provenances in South Sulawesi. (February 2019) - Larekeng, S H; Restu, M; Arif, A; Cahyaningsih, Y F; Mukti, J
Abstract: Jabon merah (Anthocephalus macrophyllus) is fast-growing species that endemic to Indonesia, particularly Sulawesi and Maluku. Studies on pollen dispersal and pollination type assist to determine whether the species suffering inbreeding depression in the population. This study investigated the mating system and pollen dispersal pattern on A. macrophyllus in its habitat distribution based on microsatellite marker (SSR). Here, we collected leaf samples from three different locations in South Sulawesi, Luwu, Wajo, and Sidrap, and conducted molecular analysis at Biotechnology and Tree Breeding Laboratory, Faculty of Forestry, Hasanuddin University, Makassar. The analyses indicated A. macrophyllus tended to do outcrossing in each evaluated population. Means of outcrossing and selfing rates observed in the populations were 76, 9% and 23, 1%, respectively. Distance pollen travel could reach up to 339 m, and the frequencies of pollinations were varied from 1 to 7 times. The findings indicate individuals of Jabon merah in the populations may not be threatened by inbreeding depression due to outcrossed pollination nature.